"The Scalpel is Passed, " a Conversation With Dr Vincent J.M. DiMaio. (September 2019) - Dana, Suzanna
Abstract : Editor's Note: This is the first article in a new series of interviews with mentors in forensic pathology. These interviews will also be recorded, and the audio files will be available online through the journal's Web site, http://links.lww.com/FMP/A31 . Abstract : Supplemental digital content is available in the text.